Early Buddhist transmission and trade networks: mobility and exchange within and beyond the Northwestern borderlands of South Asia - Neelis, Jason Emmanuel (Dynamics in the history of religions, 2011)
Road Map for Travelers. Models for the Movement of Buddhism ; Merit, Merchants, and the Buddhist Sangha ; Sources and Methods for the study of Buddhist ; Transmission ; Outline of Destinations -- Two Historical Contexts for the Emergence and Transmission of Buddhism within South Asia. Initial Phases of the Establishment of Buddhist Communities in Early India ; Legacy of the Mauryans: Asoka as Dharmaraja ; Migrations, Material Exchanges, and Cross-Cultural Transmission in Northwestern Contact Zones ; Saka Migrants and Mediators between Central Asia and South Asia ; Dynamics of Mobility during the Kusana Period ; Shifting Networks of Political Power and Institutional Patronage during the Gupta Period ; Cross-Cultural Transmission between South Asia and Central Asia, ca. 500-1000 CE -- Trade Networks in Ancient South Asia ; Northern Route (Uttarapatha) ; Southern Route (Daksinapatha) ; Seaports and Maritime Routes across the Indian Ocean -- Old Roads in the Northwestern Borderlands ; Environmental Conditions for Buddhist Transmission in Gandhara ; Gandharan Material and Literary Cultures ; Gandharan Nodes and Networks ; Routes of Buddhist Missionaries and Pilgrims to and from Gandhara ; Domestication of Gandharan Buddhism -- Capillary Routes of the Upper Indus. Geography, Economy, and Capillary Routes in a High Altitude Environment ; Graffiti, Petroglyphs, and Pilgrims ; Enigma of an Absence of Archaeological Evidence and Manifestations of Buddhist Presence -- Long-Distance Transmission to Central Asian Silk Routes and China. Silk Routes of Eastern Central Asia ; Long-distance Transmission Reconsidered -- Alternative Paths and Paradigms of Buddhist Transmission. Catalysts for the Formation and Expansion of the Buddhist Sangha ; Changing Paradigms for Buddhist Transmission within and beyond South Asia